Democratising Terai Forestry Governance: Emerging Innovations in the Western Terai Region of Nepal (Journal of Forest and Livelihood, 2009)
The Government of Nepal has had a high interest in the Terai forest in order to harness its enormous revenue potential. However, the policies and plans formulated to this end have not attained the intended results, as these have failed to fully understand the emerging complexities in the Terai. Accordingly, policy response has often been ad hoc, inconsistent and unstable, leading to confusion and conflict on Terai forest management. Drawing on the cases of three districts of Lumbini zone in the Western Terai of Nepal, this paper discusses the forest management context of Nepal Terai, and identifies key innovations that have emerged at district and local levels. It argues that these innovations have the potential for a creative transformation of forest management planning process at district and local level, and for their wider replication and diffusion. This paper also discusses key issues that need further attention so as to maximise the impact of these innovations by putting them into practice. It highlights that emerging complexity of Nepal Terai requires much wider stakeholder engagement in order to facilitate forest management planning and implementation that benefit both the government and the people. Full text is available at the ForestAction websiteDOI: http://dx.doi.org/10.3126/jfl.v8i2.2306 Journal of Forest and Livelihood 8(2) February 2009 pp.27-38